JOB CHARACTERISTICS QUALITY OF LIFE AT WORK AND ORGANIZATIONAL COMMITMENT THAT INFLUENCES ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF PERSONNEL IN INDUSTRIAL ESTATE PHRA NAKHON SI AYUTTHAYA - Supprasert, Theerasak; Amsa-ard, Phongsakorn; Mekdee, Kobchai; Kaewchur, Pornthep; Klomklaw, Kanokkarn (Journal of Social Science and Cultural, 2024)
The objectives of this research article are 1) to study the level of opinions on job characteristics and quality of life at work organizational commitment and organizational citizenship behavior of personnel in the industrial estate of Phra Nakhon Si Ayutthaya 2) to study the influence of job characteristics and quality of work life that influences organizational commitment. 3) to study the influence of job characteristics and quality of work life that influences organizational citizenship behavior of personnel in the industrial estate of Phra Nakhon Si Ayutthaya. And 4) to study the influence of organizational commitment that influences organizational citizenship behavior of personnel in the industrial estate of Phra Nakhon Si Ayutthaya which is quantitative research a questionnaire was used to collect data from 360 personnel in the industrial estate of Phra Nakhon Si Ayutthaya using stratified random sampling. Statistics used included frequency, percentage, mean and standard deviation. Relationships were analyzed using structural equations. The results of the research found that 1) the level of opinions on job characteristics quality of life at work organizational commitment and organizational citizenship behavior of personnel in the industrial estate of Phra Nakhon Si Ayutthaya. The average was at the highest level for every factor. 2) Job characteristics and quality of life at work which have a direct and positive influence on organizational commitment. 3) Job characteristics and quality of life at work which have a positive direct and indirect influence on organizational citizenship behavior of personnel in the industrial estate of Phra Nakhon Si Ayutthaya. And 4) organizational commitment which has a positive direct influence on organizational citizenship behavior of personnel in the industrial estate of Phra Nakhon Si Ayutthaya. (Chi-Square: χ2) = 129.55, df = 127, P-value = 0.41, RMSEA = 0.01, RMR = 0.01, GFI = 0.97, AGFI = 0.95